2020
DOI: 10.1371/journal.pcbi.1008288
|View full text |Cite
|
Sign up to set email alerts
|

A semi-supervised Bayesian approach for simultaneous protein sub-cellular localisation assignment and novelty detection

Abstract: The cell is compartmentalised into complex micro-environments allowing an array of specialised biological processes to be carried out in synchrony. Determining a protein’s sub-cellular localisation to one or more of these compartments can therefore be a first step in determining its function. High-throughput and high-accuracy mass spectrometry-based sub-cellular proteomic methods can now shed light on the localisation of thousands of proteins at once. Machine learning algorithms are then typically employed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…If one or more of the proteins in such a group is known to reside in a compartment that is not represented in the marker protein set, it would be possible to use this knowledge to create an additional reference compartment for the CPA procedure. Alternatively, a Bayesian approach may be helpful in detecting previously unassigned subcellular compartments . Given high enough resolution fractionation methods, it may also be possible to further subdivide the major compartments in our current classification scheme.…”
Section: Resultsmentioning
confidence: 99%
“…If one or more of the proteins in such a group is known to reside in a compartment that is not represented in the marker protein set, it would be possible to use this knowledge to create an additional reference compartment for the CPA procedure. Alternatively, a Bayesian approach may be helpful in detecting previously unassigned subcellular compartments . Given high enough resolution fractionation methods, it may also be possible to further subdivide the major compartments in our current classification scheme.…”
Section: Resultsmentioning
confidence: 99%
“…As described in the Introduction, our data includes a set of marker proteins whose subcellular niche localisations are known a priori. Thus, K is known from the outset, since we assume that we have, at least, one marker protein localising to each subcellular niche; that is, we assume that all classes are represented among our labelled data (see Crook et al (2020), for a relaxation of this assumption).…”
Section: Methodsmentioning
confidence: 99%
“…One approach is spatial subcellular proteomics , where proteins are localized to their subcellular niche using mass-spectrometry data. Bayesian approaches have been developed for biochemical fractionation-based subcellular proteomics. ,,,, Crook et al ,, demonstrated that Bayesian modeling can quantify uncertainty in protein subcellular localization and identify cases where this may correspond to multilocalizing proteins. Crook et al showed that even a Bayesian point estimate may overlook these cases, and more information is obtained by examining the full posterior distribution.…”
Section: Mainmentioning
confidence: 99%